Clinical evaluation of the addition of gentamicin to commercially prepared mycological media. - Merz, W G (1976)
A simple procedure is presented whereby an antibiotic solution can be added to prepared agar media for conversion to a selective medium to isolate fungi. Gentamicin solution was deposited onto slants of a variety of previously prepared agar media, allowed to diffuse overnight, and then the slants were inoculated with clinical specimens. Control media without gentamicin included a cycloheximide-chloramphenicol medium (CC), Sabouraud dextrose agar (SDA), and brain heart infusion agar (BHI). Of 75 specimens originating from the respiratory tract, the fungi isolated were predominantly yeast; 35, 39, and 43 were positive on CC, SDA, and SDA with gentamicin, respectively, incubated at 25 C. At 37 C, 32, 34, and 41 positive cultures were obtained with the same media, respectively. The same specimens, inoculated onto BHI with and without gentamicin, yielded 23 and 39 positive cultures, respectively. Of 90 specimens that were either urine, cutaneous, or mucocutaneous, the predominant flora again were yeasts, although on nine occasions dermatophytes were isolated. Positive cultures, 32, 34, and 41, were obtained with CC, SDA, and SDA containing gentamicin, respectively. Bacterial contamination was significantly reduced by the gentamicin, especially on BHI incubated at 37 C. None of the specimens was positive for systemically pathogenic fungi, other than species of Candida, Torulopsis, and Aspergillus. The effectiveness of varying concentrations of gentamicin was investigated by comparing growth of recently isolated bacteria. Of the bacterial isolates, 33% grew on CC, 16% grew on SDA containing gentamicin, 50 mug/ml, and 3% grew on SDA with a gentamicin concentration at 100 mug/ml. With BHI, 3% grew in the presence of 50 mug of gentamicin/ml and less than 1% grew at 100 mug of gentamicin/ml.